Empowering Students through Autonomous Education: A Case Study of Muhammadiyah Schools - Mohamad Joko Susilo (The Indonesian Institute of Science and Technology Research, 2023)
The Implementation of Education In Autonomous Muhammadiyah Schools. The implementa-tion of education in autonomous muhammadiyah schools. This study aim to describe the inde-pendence of implementation education in Muhammadiyah schools. This study uses a qualitative method. The subjects of the study consisted of elementary school committee members, school principals, teachers, staff, and Muhammadiyah junior high school students in Sleman district. Da-ta collection using interviews and documentation. Data analysis using descriptive techniques. An independent description of implementation education in Muhammadiyah schools that is not found in other schools: applying the Islamic curriculum; integrating Islamic and Muhammadiyah values in teaching and learning activities. Muhammadiyah schools are mostly established from the waqf land belonging to Muhammadiyah and also the result of independent procurement by Muhammadiyah. The existence of company-owned business entity, such as: mart, cattering, coat (school shuttle service), and other, whose management is based on information and technology to increase school income. Teachers and staff meet qualifications and competencies; quantity, and linearity. Facilities are also complete to support learning.